Celastrol Efficacy by Oral Administration in the Adjuvant-Induced Arthritis Model - Rita Cascão; Bruno Vidal; Tânia Carvalho; Inês Pascoal Lopes; Vasco C. Romão; Vasco C. Romão; João Goncalves; Luis Ferreira Moita; João Eurico Fonseca; João Eurico Fonseca (Frontiers in Medicine, 2020)
Background: We previously demonstrated that celastrol has significant anti-inflammatory and bone protective effects when administered via the intraperitoneal route. For further preclinical evaluation, an effective oral administration of celastrol is crucial. Here we aimed to study the therapeutic dose range for its oral administration.Methods: Celastrol (1–25 μg/g/day, N = 5/group) was administrated orally to female adjuvant-induced arthritis (AIA) rats after 8 days of disease induction for a period of 14 days. A group of healthy (N = 8) and arthritic (N = 15) gender- and age-matched Wistar rats was used as controls. During the treatment period, the inflammatory score, ankle perimeter, and body weight were measured. At the end of the treatment, the animals were sacrificed, blood was collected for clinical pathology, necropsy was performed with collection of internal organs for histopathological analysis, and paw samples were used for disease scoring.Results: Doses higher than 2.5 μg/g/day of celastrol reduced the inflammatory score and ankle swelling, preserved joint structure, halted bone destruction, and diminished the number of synovial CD68+ macrophages. Bone resorption and turnover were also reduced at 5 and 7.5 μg/g/day doses. However, the dose of 7.5 μg/g/day was associated with thymic and liver lesions, and higher doses showed severe toxicity.Conclusion: Oral administration of celastrol above 2.5 μg/g/day ameliorates arthritis. This data supports and gives relevant information for the development of a preclinical test of celastrol in the setting of a chronic model of arthritis since rheumatoid arthritis is a long-term disease.